High-water-conductivity natural-color bamboo fiber fluff pulp and preparation method thereof

The hemicellulose is removed through cold alkali extraction and lignin is retained, which solves the problem of slow water absorption rate of natural bamboo fiber fuzz pulp, and achieves a balance of high water conduction performance and stiffness.

CN119615660AInactive Publication Date: 2025-03-14TIANJIN UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411715323.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The current natural bamboo fiber fuzz pulp has a slow water absorption rate, making it difficult to replace the performance of bleached bamboo fiber fuzz pulp.

Method used

By performing cold alkali extraction on the natural bamboo pulp board, hemicellulose is removed, and water absorption performance is improved, while retaining lignin components to improve stiffness and hydrophobic properties.

Benefits of technology

The water absorption rate of the natural bamboo fiber fuzz pulp is significantly improved, the water absorption time is shortened, and the stiffness of the bamboo fiber and the hydrophobic properties of lignin are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615660A_ABST
    Figure CN119615660A_ABST
Patent Text Reader

Abstract

The invention provides high-water-conductivity natural-color bamboo fiber fluff pulp and a preparation method thereof, and belongs to the technical field of papermaking pulping. The preparation method comprises the following steps: S1, pre-soaking a natural-color bamboo pulp board in water, defibering fibers, balancing moisture, and measuring the moisture for later use; and S2, taking a certain amount of paper pulp according to oven dry, carrying out dipping treatment by using a sodium hydroxide solution, after reaction, filtering the pulp, collecting filtrate, and washing the pulp to obtain the fluff pulp. Lignin is retained and hemicellulose is removed through alkali extraction, so that the water absorption rate of a natural-color fluff pulp product is greatly improved because hemicellulose can be combined with cellulose and other components in paper to form a net-shaped structure which is difficult to permeate by water molecules, and the water absorption performance of the paper is limited. After the hemicellulose is removed, a water molecule permeation path in the paper is opened, and the water absorption rate is greatly improved. Due to retention of lignin, a fluid channel is smoother during water absorption, and water conductivity of the fiber is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of papermaking and pulping, and in particular to a natural-color bamboo fiber fluff pulp with high water conductivity and a preparation method thereof. Background Art

[0002] Fluff pulp is an absorbent core pulp used in personal care products (such as disposable diapers, adult incontinence products, feminine hygiene / care products, absorbent towels, etc.). Currently, the main source of fluff pulp on the market is wood pulp fiber products, but wood raw materials are in short supply. Finding an alternative to wood pulp fiber is a technical problem that needs to be solved urgently.

[0003] The method for preparing the natural color bamboo fiber fluff pulp board disclosed in the prior art retains the natural color characteristics of the raw materials. There is no bleaching, whitening agent and color developer process in the production process, which greatly reduces the damage to the environment in the production process, maintains 100% of the natural color of the plant fiber, and has the advantages of hygiene, environmental protection and safety. The lignin component retained in the product is also beneficial to improving the stiffness of the bamboo fiber. However, the fluff pulp product prepared from the natural color bamboo fiber raw material still has the disadvantage of poor performance in various aspects. In particular, the water absorption performance of the natural color bamboo fiber raw material is still far behind that of the bleached bamboo fiber raw material. At present, no solution has been found to this problem, that is, to increase its water absorption rate without bleaching and retaining the natural color characteristics of the raw material. Summary of the invention

[0004] The purpose of the present invention is to provide a highly water-conductive natural bamboo fiber fluff pulp and a preparation method thereof in view of the above-mentioned deficiencies in the prior art, and to obtain a fluff pulp product with excellent water-conducting properties by extracting hemicellulose from a natural bamboo pulp board through cold alkali extraction. On the one hand, the lignin component in the fluff pulp product is retained, so that the bamboo fiber retains better stiffness, while the hydrophobic properties of the lignin component are also retained, so that the fluid channel is smoother during water absorption, which is beneficial to the water conductivity of the fiber. On the other hand, the water absorption performance of the obtained product is improved by cold alkali extraction treatment, which greatly shortens the water absorption time of the natural bamboo fiber fluff pulp product. The technical problem of the slow water absorption rate of the natural bamboo fiber fluff pulp in the prior art is solved.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The first object of the present invention is to provide a method for preparing high water-conductivity natural color bamboo fiber fluff pulp, comprising the following steps:

[0007] S1. Soak the natural bamboo pulp board in water in advance to loosen the fibers, balance the water content, and measure the water content for later use;

[0008] S2. Taking a certain amount of pulp on an absolute dry basis, soaking it in a sodium hydroxide solution, filtering the pulp after the reaction, collecting the filtrate, and washing the pulp to obtain fluff pulp.

[0009] Furthermore, in step S2, the mass concentration of sodium hydroxide is 5% to 15%.

[0010] Furthermore, the temperature of the immersion treatment is 10°C to 25°C.

[0011] Furthermore, the immersion treatment time is 25 to 50 minutes.

[0012] Furthermore, the mass concentration of the slurry is 5-10%.

[0013] The second object of the present invention is to provide a fluff pulp prepared by the above-mentioned preparation method.

[0014] The third object of the present invention is to provide a fluff pulp product, wherein the fluff pulp is placed in a fiber defibering machine and dispersed evenly, and then a certain amount of pulp sheets are made on a rapid paper sheet former. After the pulp sheets are dried, dry dissociation is performed through a raising device to obtain a fluff pulp product.

[0015] Furthermore, the basis weight of the pulp sheet is 200 to 650 g / m 2 .

[0016] Furthermore, the drying method is vacuum drying or drying at 100-105°C.

[0017] Furthermore, the moisture content of the dried pulp sheet is 7% to 9%.

[0018] The calculation of absolute dryness is as follows: take a certain amount of fiber and weigh it, record it as w1 (in g). Put it into a 105℃ oven and dry it to constant weight, take it out and weigh it, record it as w2 (in g).

[0019] The moisture content of the fiber X (%) is calculated as: X = (w1-w2) / w1×100

[0020] When taking fiber, the moisture content of the fiber is used to convert its weight to absolute dry weight.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention provides a method for preparing natural-color bamboo fiber fluff pulp with high water conductivity. The water absorption time of the natural-color fluff pulp product is greatly reduced and its water absorption rate is increased through alkaline extraction treatment. This is because the hemicellulose removed in this process will combine with cellulose and other components in the paper to form a network structure that is difficult for water molecules to penetrate, thereby limiting the water absorption performance of the paper. After the hemicellulose is removed, the water molecule penetration path in the paper is opened and the water absorption rate is greatly improved. At the same time, the retained lignin component, due to its own hydrophobic properties, the presence of lignin can form a smoother fluid channel on the fiber surface during the fiber water absorption process, thereby reducing obstacles to fluid flow and helping to increase the fiber's water absorption rate.

[0023] (2) Using natural bamboo pulp board as raw material, the dispersed plant fiber obtained after decomposition provides higher accessibility than bamboo chip raw material, effectively improving the reaction efficiency of alkali treatment. The alkali impregnation treatment temperature only needs 10-25℃, and the treatment time only needs 25-50min. It is easy to operate and easy to mass produce. The single use of chemicals reduces the difficulty of waste liquid treatment and increases the value of filtrate reuse. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The infrared spectra of different bamboo fiber samples are compared. In the figure, a is the bleached chemical pulp fluff fiber of Cibaba cirrhosae without alkali treatment, b is the natural chemical-mechanical pulp fluff fiber of Cibaba cirrhosae without alkali treatment, c is the natural chemical-mechanical pulp fluff fiber of Cibaba cirrhosae with 10% alkali concentration treatment, and d is the natural chemical-mechanical pulp fluff fiber of Cibaba cirrhosae with 14% alkali concentration treatment.

[0025] Figure 2 This is the infrared spectrum of natural bamboo chemical-mechanical pulp fluff fiber with different amounts of debonding agent added. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the present invention clearer, embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0027] The reagents and experimental materials used in the present invention can be obtained commercially.

[0028] In this embodiment, the natural color machine bamboo pulp board raw materials and bleached chemical bamboo pulp board raw materials are all from a paper mill in Sichuan. The natural color machine bamboo pulp board raw materials are pulp obtained by simple chemical treatment and mechanical treatment, without bleaching treatment, and the pulp board color is the original color of plant fiber.

[0029] Bleached chemical bamboo pulp board is made of pulp obtained through chemical treatment and bleaching, without mechanical treatment. The color of the pulp board is white.

[0030] The fiber detangling machine used in this embodiment is from Lorentzen & Wettre, Sweden, model 9701054, the semi-automatic fast hand sheeting machine is from PTI, Austria, model RK-ZA-KWT, and the raising equipment is Royalstar brand, model: RS-FS1411.

[0031] Example 1

[0032] This embodiment provides a method for preparing high water-conductivity natural color bamboo fiber fluff pulp, and the specific steps are as follows:

[0033] Soak the natural bamboo pulp board in water for 4 hours in advance, and use a standard deflaking machine to deflake the fibers according to standard QB / T1462-1992, then balance the moisture for 24 hours, and measure its moisture for use. Take 70g of pulp (absolutely dry) and treat it with 5% sodium hydroxide concentration at 25°C for 45 minutes, and keep the pulp concentration at 5%. In order to make the pulp and sodium hydroxide react evenly, manual kneading is required. After the reaction, filter the pulp, collect the filtrate, and wash the pulp to obtain fluff pulp.

[0034] Referring to ISO 5269-1:2005, a certain amount of the above fluff pulp was weighed and dispersed evenly in a fiber deflaker, and then transferred to a standard paper sheet former and made into sheets using a semi-automatic fast hand sheeter with a basis weight of 250 g / m 2 The paper-made pulp sheet is placed in the vacuum dryer of the rapid paper former equipment and dried at 95°C for 15 minutes. The moisture content of the pulp sheet is finally maintained between 7% and 9%. The paper-made pulp sheet is dry-dissociated through the napping equipment to obtain the fluff pulp product.

[0035] The dry bulkiness of the fluff pulp product prepared in the present embodiment is 18.658 cm 3 / g, the water absorption time is 7.22s, and the water absorption amount is 9.24g / g.

[0036] Among them, the fluff pulp performance test method refers to: GB / T 21331-2021.

[0037] Example 2

[0038] This embodiment provides a method for preparing natural color bamboo fiber fluff pulp with high water conductivity, which is basically the same as that of Embodiment 1, except that 10% sodium hydroxide is added for treatment.

[0039] The dry bulkiness of the fluff pulp product prepared in the present embodiment is 20.13 cm 3 / g, the water absorption time is 4.92s, and the water absorption amount is 9.70g / g.

[0040] Among them, the fluff pulp performance test method refers to: GB / T 21331-2021.

[0041] Example 3

[0042] This embodiment provides a method for preparing natural-color bamboo fiber fluff pulp with high water conductivity, which is basically the same as that of Embodiment 1, except that 6% sodium hydroxide is added for treatment.

[0043] The dry bulkiness of the fluff pulp product prepared in this embodiment is 19.39 cm 3 / g, the water absorption time is 7.84s, and the water absorption amount is 9.67g / g.

[0044] Among them, the fluff pulp performance test method refers to: GB / T 21331-2021.

[0045] Example 4

[0046] This embodiment provides a method for preparing natural-color bamboo fiber fluff pulp with high water conductivity, which is basically the same as that of Embodiment 1, except that 14% sodium hydroxide is added for treatment.

[0047] The dry bulkiness of the fluff pulp product prepared in this embodiment is 19.15 cm 3 / g, the water absorption time is 6.80s, and the water absorption amount is 9.22g / g.

[0048] Among them, the fluff pulp performance test method refers to: GB / T 21331-2021.

[0049] Comparative Example 1

[0050] The natural color machine bamboo pulp board raw material used has not been treated with alkali impregnation. After soaking and debonding, it is re-made into 250g / m 2 The dry bulk of the quantitative pulp sheet after dry dissociation by the same fluffing equipment is 17.28cm 3 / g, the water absorption time is 8.26s, and the water absorption amount is 8.88g / g.

[0051] Among them, the fluff pulp performance test method refers to: GB / T 21331-2021.

[0052] Comparative Example 2

[0053] The bleached chemical bamboo pulp board raw materials used have not been treated with alkali impregnation. After soaking and degassing, they are re-made into 250g / m 2 The dry bulk of the quantitative pulp sheet after dry dissociation by the same fluffing equipment is 20.6cm 3 / g, water absorption time is 4.4s, and water absorption amount is 10.2g / g.

[0054] Among them, the fluff pulp performance test method refers to: GB / T 21331-2021.

[0055] Comparative Example 3

[0056] The natural color machine bamboo pulp board raw material used has not been treated with alkali impregnation. After soaking, 0.3% debonding agent is added during debonding and re-made into 250g / m 2 The dry bulk of the quantitative pulp sheet after dry dissociation by the same fluffing equipment is 18.99cm 3 / g, the water absorption time is 17.06s, and the water absorption amount is 9.01g / g.

[0057] Among them, the fluff pulp performance test method refers to: GB / T 21331-2021.

[0058] Comparative Example 4

[0059] The natural color machine bamboo pulp board raw material used has not been treated with alkali impregnation. After soaking, 0.5% debonding agent is added during debonding and re-made into 250g / m 2 The dry bulk of the quantitative pulp sheet after dry dissociation by the same fluffing equipment is 18.66cm 3 / g, the water absorption time is 18.42s, and the water absorption amount is 9.11g / g.

[0060] Among them, the fluff pulp performance test method refers to: GB / T 21331-2021.

[0061] Comparative Example 5

[0062] The natural color machine bamboo pulp board raw material used has not been treated with alkali impregnation. After soaking, 1% debonding agent is added during debonding and re-made into 250g / m 2 The dry bulk of the quantitative pulp sheet after dry dissociation in the same fluffing equipment is 19.15m 3 / g, the water absorption time is 17.30s, and the water absorption amount is 8.65g / g.

[0063] The above mentioned debonding agents are all Varisoft 3696 debonding agents, manufactured by Evonik.

[0064] By comparing Example 2 with Comparative Example 1, it can be seen that the water absorption time of the treated natural fluff pulp product is reduced from 8.26s to 4.92s, almost half, which greatly improves the water absorption rate and narrows the performance gap with the bleached fluff pulp product. The water absorption amount is also improved. As for the difference in raw materials, the bleached chemical pulp of Comparative Example 2 has a lower content of lignin than the unbleached chemical pulp of Comparative Example 1, which is beneficial to the water absorption performance of the fluff pulp. However, the natural unbleached chemical pulp treated with cold alkali has both a low content of hemicellulose and a high content of lignin. The synergistic effect of the two greatly improves the water absorption rate. Although the fluff pulp products prepared from bleached pulp still have better fluff pulp properties, this may be because the removal of lignin increases the water absorption of the fiber, which can be reflected in its excellent water absorption data. In the state of fluff fiber, the product obtained from the bleached pulp raw material has a shorter water absorption time. This is because when the fibers are dispersed and stacked, the hydrophobicity of lignin has a smaller effect, so that the obtained fluff pulp product still has a lower water absorption time. However, in the case of backing paper made of fluff pulp, the effect is completely opposite, as can be shown by the test results of the Krem water absorption rate described later.

[0065] Performance characterization:

[0066] (1) The results of fiber morphology analysis are shown in Table 1:

[0067] Table 1. Fiber morphology analysis results

[0068]

[0069] As can be seen from the table, the fluff pulp treated with alkali (Example 2) has a significantly lower aspect ratio and higher kink angle, kink index and curl index than the fluff pulp obtained from the same material without treatment (Comparative Example 1). The increase in kink angle, kink index and curl index reaches the same degree or even greater than that of the fluff pulp obtained from the bleached raw material (Comparative Example 2).

[0070] From the comparison of the fluff pulp performance parameters of Example 2 and Comparative Example 1, it can be seen that the water absorption of the natural color fluff pulp product after treatment is increased from 8.88g / g to 9.7g / g. It can be seen from the above table that this may be related to the increase of the kink angle, kink index and curl index, which is closer to the parameters of the bleached fluff pulp product (Comparative Example 2), but there is still a certain gap with the water absorption of 10.2g / g of the bleached fluff pulp product (Comparative Example 2). This may be due to the low content of lignin in the fiber of the bleached fluff pulp product itself. It is generally believed that the water absorption of fluff pulp is mainly affected by the three-dimensional structure and porosity of the fiber. A larger aspect ratio of the fiber, as well as a larger kink angle, kink index and curl index may be beneficial to the pores between the fibers, so that the fluff balls have a larger dry bulk and water absorption. Although the aspect ratio of the treated fiber (Example 2) is reduced, the fiber kink angle, kink index, and curl index change more greatly, which may make up for the defect of the aspect ratio, so that the dry bulkiness and water absorption are still improved.

[0071] (2) Infrared spectra of different bamboo fiber samples

[0072] like Figure 1 The following are infrared spectra of different bamboo fiber samples. In the figure, a is the untreated bleached chemical pulp fluff fiber of Cibaba cirrhosae, b is the untreated natural chemical pulp fluff fiber of Cibaba cirrhosae, c is the untreated natural chemical pulp fluff fiber of Cibaba cirrhosae with 10% alkali concentration, and d is the untreated natural chemical pulp fluff fiber of Cibaba cirrhosae with 14% alkali concentration. -1 The prominent band near 3400 cm represents the OH stretching vibration. Alkaline treatment with sodium hydroxide induces synergistic interactions between hydrogen bond acceptors and donors, thus disrupting the bond between cellulose and hemicellulose at 3400 cm -1 The original hydrogen bonds at 3400cm -1 The peak at 2900 cm-1 indicates that the hemicellulose content in the holocellulose is higher and has more types of hydroxyl peaks. -1 The signal is generated at 2900cm -1 The broad peak at 3400cm represents the CH stretching vibration of methyl and methylene groups in hemicellulose. -1 and 2900cm -1The number of peaks near 1047cm-1 has decreased. Hemicellulose is generally considered to be hydrophilic. In theory, the reduction of hemicellulose means the reduction of the number of hydroxyl groups, which is not conducive to the water absorption performance of the fiber. However, the performance of the sample obtained in this application is the opposite. This may be due to the fact that the removal of hemicellulose has an impact on the fiber cell wall, which has caused changes in the fiber surface structure. It can also be found in the figure that although the number of hemicelluloses has decreased, the peak intensity has increased slightly, which may be due to the increase in hydroxyl activity. At 1047cm-1 -1 The strong band at 3400cm comes from the COC bond between the glycosidic bonds of the sugar units. -1 and 1047cm -1 The two bands indicate the presence of a large number of OH and COC bonds in all samples. -1 The band at 1640 cm indicates that it is associated with bound lignin. The disappearance of the band at this point in the figure indicates that there is no associated lignin. -1 The strong absorption band at 897cm corresponds to the bending mode of water absorption, because hemicellulose generally has a strong affinity for water, and in the solid state these macromolecules may have a disordered structure and can be easily hydrated. The peak intensity here in the figure is large, which is consistent with the water absorption rate performance of the sample. -1 The absorption band at is considered to be the COC stretching of the β-(1-4)-glycosidic bond, which is usually weak and broad in cellulose I, but strong and sharp in cellulose II and amorphous cellulose. As shown in Figures b, c, and d, the peak here is slightly enhanced with the increase of alkali concentration.

[0073] like Figure 2 The figure shows the infrared spectra of natural bamboo chemical-mechanical pulp fluff fibers with different amounts of debonding agents added. Debonding agents are agents that weaken the bonding of fibers and can weaken the bonding between hydrogen bonds. Figure 2 It can be seen that with the addition of debonding agent, each absorption peak gradually weakened, proving its ability to shield hydroxyl groups. However, the addition of debonding agent is not conducive to the water absorption performance of fluff fiber. For example, after testing, the water absorption time of fluff fiber with 0.3% debonding agent added reached 17.06s (the water absorption time of fluff fiber without debonding agent was 8.26s). It can be seen that the shielding of hydroxyl groups has a great influence on the water absorption performance of fluff fiber. However, the removal of hemicellulose can increase its water absorption performance, which may be related to the effect of alkali treatment on the surface structure of the fiber and the activity of its surface hydroxyl groups.

[0074] (3) Comparison of water absorption and physical properties of the liner paper prepared from the obtained fluff pulp

[0075] Use the treated fluff pulp to make a certain amount of paper sheets through a semi-automatic fast hand sheet machine, and measure the water absorption of the paperboard with reference to GB / T461.1-2002. The paper water absorption tester is also called the Krem tester, which is suitable for the determination of the capillary absorption height of unsized paper and paperboard.

[0076] Through measurement, we can get:

[0077] The water absorption height of the natural color backing paper strips without alkali treatment is 72.40mm at 2min; 105.40mm at 5min; and 140.50mm at 10min.

[0078] The water absorption height of the natural color backing paper strip treated with 6% alkali concentration is 78.80mm at 2min, 110.40mm at 5min, and 144.00mm at 10min.

[0079] The water absorption height of the natural color backing paper strip treated with 10% alkali concentration is 98.20mm at 2min, 142.40mm at 5min, and 182.20mm at 10min.

[0080] The water absorption height of the white liner paper made of bleached chemical pulp without alkali treatment was 65.00 mm at 2 min, 96.00 mm at 5 min, and 129.0 mm at 10 min.

[0081] It can be seen that the water absorption performance of the treated natural color backing paper is significantly improved. The water absorption height of the sample treated with 10% alkali concentration increased by 35.6% at 2 minutes, 35.1% at 5 minutes, and 29.7% at 10 minutes. However, the backing paper prepared from the bleached chemical bamboo pulp raw material with a shorter water absorption time in the state of fluff fibers has a lower water absorption height at the same time. This proves that in the case of backing paper, due to the more regular and fixed fiber arrangement, the role of lignin in the fluid channel is more obvious. The removal of hemicellulose and the retention of lignin, the synergistic effect of the two makes the prepared fluff pulp product greatly improve the water absorption rate of the fiber not only in the state of backing paper but also in the state of fluff fibers, and increase the water conductivity of the fiber.

[0082] As a comparison, the properties of the liner paper prepared by adding a debonding agent were also measured:

[0083] The water absorption height of the natural color backing paper strips without alkali treatment is 72.40mm at 2min; 105.40mm at 5min; and 140.50mm at 10min.

[0084] The water absorption height of the natural color backing paper strip with 0.1% debonding agent added is 56.80mm at 2min, 80.00mm at 5min, and 104.00mm at 10min.

[0085] The water absorption height of the natural color backing paper strip with 1% debonding agent added is 50.40mm at 2min, 69.60mm at 5min, and 89.60mm at 10min.

[0086] It can be seen that the water absorption performance of the natural color backing paper with the addition of debonding agent is significantly reduced.

[0087] (4) Physical properties testing

[0088] The bursting index of natural lining paper without alkali treatment is 0.94 kPa·m 2 / g; the tensile index is 19.51N·m / g; and the zero-span tensile strength of the fiber is 70.70N / cm.

[0089] The tear resistance index of the natural lining paper treated with 6% alkali concentration is 0.64kPa·m 2 / g; the tensile index is 12.53N·m / g; and the zero-span tensile strength of the fiber is 67.58N / cm.

[0090] The bursting index of the natural lining paper treated with 10% alkali concentration is 0.37 kPa·m 2 / g; the tensile index is 6.39N·m / g; and the zero-span tensile strength of the fiber is 53.46N / cm.

[0091] The bursting index of the natural color lining paper with 0.1% debonding agent added is 0.82 kPa·m 2 / g; the tensile index is 13.53N·m / g; and the zero-span tensile strength of the fiber is 71.04N / cm.

[0092] The bursting index of the natural color lining paper with 1% debonding agent added is 0.66 kPa·m 2 / g; the tensile index is 12.24N·m / g; and the zero-span tensile strength of the fiber is 67.09N / cm.

[0093] Through the test results of the physical properties of the prepared backing paper, it was found that the natural backing paper treated with 6% alkali concentration can achieve the same physical performance parameters as the natural backing paper with 1% debonding agent. In this case, the water absorption height and water absorption rate of the paper strip increased significantly, while the latter decreased significantly. The strength performance of paper can reflect the interweaving between fibers, while zero-span tensile strength can reflect the strength of the fiber itself. Adding debonding agents can reduce the burst resistance of paper and improve the dry bulkiness of fluff pulp products, which has been a common method used by predecessors. However, the physical strength of paper prepared by alkali-treated fibers is lower, and the effect is more significant than that of using debonding agents, and it can also increase the water absorption rate of the product. This may be because the alkali-treated fibers have changed at the cell wall level, causing changes in the structure and hydroxyl situation of the fibers, which is not conducive to the change of paper strength and promotes the water absorption capacity of the fibers at the same time. This change in the physical properties of the paper is just conducive to meeting the requirements of fluff pulp for dry bulkiness, and also meets the requirements of fluff fibers for high bulkiness and high water absorption. This significantly improves the performance of natural fluff pulp products.

[0094] For matters not mentioned above, the prior art applies.

[0095] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make modifications or supplements to the described specific embodiments or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above implementations based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high water-conductivity natural color bamboo fiber fluff pulp, characterized in that: The following steps are involved: S1. Soak the natural bamboo pulp board in water in advance to loosen the fibers, balance the water content, and measure the water content for later use; S2. Taking a certain amount of pulp on an absolute dry basis, soaking it in a sodium hydroxide solution, filtering the pulp after the reaction, collecting the filtrate, and washing the pulp to obtain fluff pulp.

2. The preparation method according to claim 1, characterized in that In step S2, the mass concentration of sodium hydroxide is 5% to 15%.

3. The preparation method according to claim 2, characterized in that: The temperature of the immersion treatment is 10°C to 25°C.

4. The preparation method according to claim 3, characterized in that: The immersion treatment time is 25 to 50 minutes.

5. The preparation method according to claim 4, characterized in that: The mass concentration of the slurry is 5-10%.

6. Fluff pulp prepared by the preparation method according to any one of claims 1 to 5.

7. A fluff pulp product, characterized in that: The fluff pulp described in claim 6 is dispersed uniformly, and then a certain amount of pulp sheets are made. After the pulp sheets are dried, dry dissociation is performed through a raising device to obtain a fluff pulp product.

8. The fluff pulp product according to claim 7, characterized in that The basis weight of the pulp sheet is 200-650 g / m 2 .

9. The fluff pulp product according to claim 8, characterized in that The drying method is vacuum drying or drying at 100-105°C.

10. The fluff pulp product according to claim 9, characterized in that The moisture content of the dried pulp sheet is 7% to 9%.

Citation Information

Patent Citations

  • Clean preparation method of high-quality and high-purity natural-color bamboo fluff pulp

    CN106192542A

  • Production process for fluff pulp for pad core layer in sanitary pad

    CN106510970A

  • Bamboo fiber fluff pulp as well as preparation method and application thereof

    CN113789680A

  • Natural color bamboo fiber fluff pulp board and preparation method thereof

    CN116623457A

  • Absorbent products and methods of preparation thereof

    US20020096276A1